PENGARUH SENAM NIFAS TERHADAP PROSES INVOLUSI UTERI PADA IBU POST PARTUM DI BPM Hj.NINIK ARTININGSIH, SST.M.KES WILAYAH BLOOTO KOTA MOJOKERTO - Dewi Yanti, Ariu (JURNAL KEPERAWATAN BINA SEHAT, 2014)
Motivation is a physiologi and psychologi condition in a someone that motivate to do certain activity in order to reach out for direction( necessity). The motivations function is to motivate someone to do certain activity. Its also as an activate or a motor that give energy to someone to do assignment. This research is to get the description of nifas mothers description to follow nifas gym in BPM Hj.Ninik Artiningsih, SST.M.Kes, Blooto Mojokerto district. The research is use descriptive methode, the population are 29 respondens. It’s take by consecutive sampling. the data is take by quetioner in April – Mei 2013. Then the data is analize by editing, coding,scoring and tabulating. The result of the research shows. That the motivation of nifas mother to follow nifas gym is medium and the total is 16 (55,2%) respondens. Motivation are influences by the age, educations level, occupations and parity of respondens. From these conclution, its better for respondens to improve their proclivity to look for information through healthy cares place, mass media and electronic media in order that they can improve their knowledge about nifas gym, and motivate to follow nifas gym.Key words : Motivation, Nifas Periode, Nifas gym.